1965
DOI: 10.1007/bf02635582
|View full text |Cite
|
Sign up to set email alerts
|

Methods for the determination of cyclopropenoid fatty acids V. A spectrophotometric method for cottonseed oils based upon the Halphen‐test reaction

Abstract: A spectrophotometric method of analysis for the quantitative estimation of cyclopropenoid fatty acids in cottonseed oil based upon the Halphen‐test reaction has been described. Various parameters involved in the reaction have been investigated and two pigment fractions responsible for the characteristic Halphen‐test cherry‐red color have been isolated. The method is applicable to relatively small amts of sample material. The average deviation from the actual cyclopropenoid acid contents as determined by the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1965
1965
1993
1993

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 6 publications
0
7
0
1
Order By: Relevance
“…Compounds 2, 5, and 6 have equivalent chain lengths (ECL) of 19.24, 17.29, and 17.24 on the Carbowax 20M, respectively. Pure dihydromalvalic acid (3) was prepared by oxidation of 2 using the Barbier Wieland oxidation method (Bailey et al, 1965). Using CPFA 3 as starting material, compounds 6-9 were obtained in the same manner.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compounds 2, 5, and 6 have equivalent chain lengths (ECL) of 19.24, 17.29, and 17.24 on the Carbowax 20M, respectively. Pure dihydromalvalic acid (3) was prepared by oxidation of 2 using the Barbier Wieland oxidation method (Bailey et al, 1965). Using CPFA 3 as starting material, compounds 6-9 were obtained in the same manner.…”
Section: Resultsmentioning
confidence: 99%
“…Dihydromalvalic acid (3) was obtained (97 % purity by GC) by Barbier Wieland oxidation using Grignard reagents (Bailey et al, 1965). A mixture containing CPFA 6-9 was obtained by using the same oxidation method, starting from dihydromalvalic acid.…”
Section: Methodsmentioning
confidence: 99%
“…( 2) fered from that of reduced Fl; (iv) NMR spectrum of Fl showed a triplet at 5.3 ppm. This indicated that an ethylenic bond was present in the molecule (10) and eliminated the possibility that Fl contained the structure below.…”
Section: Ch2mentioning
confidence: 93%
“…1017. test were obtained pure by vapor phase chromatography employing a gas chromatograph column packed with 15% Carbowax 20M suspended on Chromosorb W. Tetramethylallene does not give a positive test. No color is developed when the test is run in amyl alcohol (Halphen, 1897) or in butyl alcohol (Bailey et al, 1965). The visible spectra of the positive tests were obtained and compared with the visible spectrum of a positive Halphen obtained from refined cottonseed oil.…”
mentioning
confidence: 99%